Islam Memandang Asuransi - Muh Fudhail Rahman (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
Insurance is an effort of anticipating the life to reduce the risks that can arise at any time in human beings in the future. Islam also have warned people to prepare for a better tomorrow. Insurance began to be developed in the western world in the system of human life since decades. However, fundamentally, a lot of things on the way along with the other financial institutions that are not in line of Sharia principles. Even in their own insurance there are new innovations in its development trajectory that increasingly can not escape from Maysir (gambling), Gharar (deceit) and Riba (interest). Therefore, insurance have become essential human needs, including Muslims, it is very important to know what has been formulated by Muslim scolars associated with the implementation of systems and mechanisms Islamic insurance which is in line with the values of Islam.